Azadirachta indica acts as a pro‐oxidant and modulates cell cycle associated proteins during DMBA/TPA induced skin carcinogenesis in mice. (11th October 2012) - Arora, N.; Bansal, M. P.; Koul, A.
<x xml:space="preserve">Abstract</x> The present study was designed to determine the modulatory effect of aqueous Azadirachta indica leaf extract (AAILE) on cell cycle–associated proteins during two‐stage skin carcinogenesis in mice. Considering the dual role of reactive oxygen species in cancer and its chemoprevention, the levels of lipid peroxidation (index of peroxidative damage) were also determined. Skin tumours were induced by topical application of 7, 12‐dimethylbenz(a)anthracene (DMBA) as a carcinogen followed by the repetitive application of 12‐O‐tetradecanoylphorbol‐13‐acetate (TPA) as a promoter. Skin tumours obtained in the DMBA/TPA group exhibited enhanced expression of proliferating cell nuclear antigen (PCNA, index of proliferation), p21 and cyclin D1, with no alterations in p53 expression in comparison to the control group. Tumours in AAILE + DMBA/TPA group exhibited low PCNA and cyclin D1 expression and enhanced expression of p53 and p21 in comparison to the DMBA/TPA group. The skin tumours obtained in the AAILE + DMBA/TPA group exhibited high lipid peroxidation levels in comparison to the tumours obtained in the DMBA/TPA group. The observations of the present study suggest that AAILE behaves as a pro‐oxidant in the tumours, thereby rendering them susceptible to damage, which eventually culminates into its anti‐neoplastic action. Also, cell cycle regulatory proteins may be modulated by AAILE and could affect the progression of cells through the cell cycle. Copyright © 2012 John Wiley & Sons, Ltd.